Shared associations identify causal relationships between gene expression and immune cell phenotypes - Christiane Gasperi (Nature Portfolio, 2021)
Christiane Gasperi et al. used a shared association mapping approach to identify pairs of immune cell traits and gene expression traits showing shared genetic associations. Using polygenic risk score analysis and Mendelian randomization approaches, they find that while many such shared associations indicate a causal relationship between traits, observation of overlapping genomic associations alone is not sufficient to infer causality.